Efektivitas Model Pembelajaran Problem-Based Learning dalam Meningkatkan Hasil Belajar IPA dan Motivasi Siswa - Dewi , Shinta; Munali; Haratua, Chandra Sagul; Siti Alifah (Journal of Practice Learning and Educational Development, 2025)
The objectives of this study are: (1) to describe the motivation of students at SMPN IV Subang in terms of the problem-based learning model, (2) to determine the effect of the problem-based learning model on the science learning outcomes of students at SMPN IV Subang. This study is a descriptive and quantitative experimental study. The subjects in this study were eighth-grade students at SMPN 4 Subang. The data collection techniques used were science achievement tests and learning motivation questionnaires. The data analysis techniques used were descriptive statistical analysis of percentages for student learning motivation data, while to examine the effect of the problem-based learning model on the science achievement of students at SMPN IV Subang, an independent two-sample t-test was used. The results of this study indicate that most students fall into the very high motivation category (38.5%), while the group of students given the conventional learning model mostly fall into the moderate motivation category (46.2%). For the hypothesis test on the effect of the problem-based learning model, the sig score was 0.000 < 0.05, so Ho was rejected and H1 was accepted, concluding that there was a difference in science learning outcomes between the group of students taught using the problem-based learning model and the group of students taught using the conventional learning model.